Photoluminescence, Self cleaning and Photocatalytic Behavior of Waterborne Hyperbranched Polyester/Carbon dot@TiO2 Nanocomposite. Issue 22 (11th June 2018) - Hazarika, Deepshikha; Saikia, Devabrata; Gupta, Kuldeep; Mandal, Manabendra; Karak, Niranjan
Abstract: Functional materials with innovative optical features have attracted cumulative attention owing to their indispensable and inimitable roles in the advanced human‐civilization. Thus, in the present work, an excellent excitation wavelength dependent down‐ and up‐conversion photo‐luminescent carbon dot@TiO2 containing waterborne hyperbranched polyester nanocomposite was reported for the first time. Further, the thermosets of the nanocomposite were transparent and emitted different colors on exposure of different wavelengths of UV light. Most interestingly, the nanocomposite showed anti‐reflecting as well as self‐cleaning properties. The self‐cleaning behavior was achieved through photocatalytic degradation of different organic contaminants namely pesticide, phenol, bis‐phenol A and mixed dyes under normal sunlight. Further, the thermosetting nanocomposite can be used as an efficient photocatalyst for reduction of common nitro‐aromatic compound under normal sunlight. The nanocomposites also exhibited strong antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae and Pseudomonas aeruginosa bacterial strains. Thus, the studied nanocomposite has remarkable prospect in different advanced applications. Abstract : Different optical properties of bio‐based waterborne hyperbranched polyester nanocomposites with carbon dot@TiO2, were reported for the first time. These nanocomposites exhibited both wavelength dependent down‐ and up‐conversion photoluminescence properties and emitted green‐blue colors on exposure of UV light with different wavelengths. Most interestingly, they showed some fascinating properties like anti‐reflecting, self‐cleaning and photocatalytic activity. Furthermore, antibacterial activity against different bacterial strains such as Staphylococcus aureus, Klebsiella pneumonia, Bacillus subtilis, and Pseudomonas aeruginosa was observed for the nanocomposites.